(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2025)
Background: In CKD patients, the leading cause of mortality is cardiovascular disease. In most cases, it is related to vascular calcification. Among multiple risk factors for vascular calcification, decline of Residual Renal Function (RRF) is an important one. So far, data are scarce regarding this. To determine the association between vascular calcification and low RRF in HD patients. Materials and methods: An observational study was performed on 60 CKD patients on MHD with low RRF attend ing in dialysis units of Chittagong Medical College Hospital in Bangladesh during the period from April 2018 to March 2019. Blood samples for biochemical analysis were collected in fasting condition and lateral lumbar radiography was done for vascular calcification score. Data were analysed using SPSS version 20. Continuous variables were expressed as mean and standard deviation, or as median and interquartile range according to distribution. Categorical variables were expressed as frequency distribution. Statistical analysis included unpaired t test for quantitative variables and c test for categorical variables. To assess the individual and combined influence of variables on Abdominal Aortic Calcification (AAC) score, univariate and multivariate linear regression were used respectively. Data were presented in tables and figures. Statistical significance was defined as p<0.05 and confidence interval set at 95% level. Results: The prevalence of vascular calcification was present in 88.3% cases in patients with low RRF and the 2 association was significant. There was also positive correlation of vascular calcification with FBS, CRP, iPTH, Cholesterol, BMI, serum calcium, serum phosphate, Ca x PO4 product and systolic BP but it was negative for serum Albumin, diastolic BP. Conclusion: Vascular calcification is very common in patients with ESRD on MHD. Loss of RRF may be an important risk factor for vascular calcification. JCMCTA 2025 ; 36 (1) : 56-60